2007
DOI: 10.1016/j.ijmecsci.2006.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of porosity on cavitation instability predictions for elastic–plastic solids

Abstract: Cavitation instabilities have been found for a single void in a ductile metal stressed under high triaxiality conditions. Here, the possibility of unstable cavity growth is studied for a metal containing many voids. The central cavity is discretely represented, while the surrounding voids are represented by a porous ductile material model in terms of a field quantity that specifies the variation of the void volume fraction in the surrounding metal. As the central void grows, the surrounding void volume fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…4 shows a clear difference between the curves for the the five different initial geometries of the central voids analysed. As was discussed in [5] for the initially spherical void, the rapid load drop at 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Fig. 5b shows that rapid void growth has started from the sharp end of the surface of the central void.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…4 shows a clear difference between the curves for the the five different initial geometries of the central voids analysed. As was discussed in [5] for the initially spherical void, the rapid load drop at 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Fig. 5b shows that rapid void growth has started from the sharp end of the surface of the central void.…”
Section: Resultsmentioning
confidence: 90%
“…For strain controlled nucleation, Chu and Needleman [18] have proposed the following expressions for the nucleation coefficients A and B The analyses in [5] accounted for the dependence of elastic properties on porosity, by using expressions derived by Tandon and Weng [19], but it was found that this reduced elastic stiffness had negligible effect. Very similar results were obtained by using linear interpolations of the expressions for…”
Section: Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations